2021
DOI: 10.3390/app11052181
|View full text |Cite
|
Sign up to set email alerts
|

Combining Chemical Composition Data and Numerical Modelling for the Assessment of Air Quality in a Mediterranean Port City

Abstract: The aim of this study is to characterize the air quality in a Mediterranean port city. The impact of ship emissions on both gaseous and particulate pollutants has been investigated through an integrated methodology which includes atmospheric flow and dispersion numerical modelling as well as chemical composition and statistical analyses. Specifically, chemical compositional data (ionic fraction, carbonaceous compounds, and metals) of PM2.5 were acquired during an experimental field campaign carried out in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…To control the concentrations of O3 and PM, a series of regulations and policies related to VOCs should be better implemented. In Cesari et al [2], the impact of ship emissions on both gaseous and particulate pollutants has been investigated through an integrated methodology which includes atmospheric flow and numerical dispersion modelling as well as chemical composition and statistical analyses. BOLCHEM results showed that the impact of ship emissions covered an area of a few dozen kilometers and was 37.6% for NOx, −11.7% for O3, 4.3% for PM10, and 6.1% for PM2.5.…”
mentioning
confidence: 99%
“…To control the concentrations of O3 and PM, a series of regulations and policies related to VOCs should be better implemented. In Cesari et al [2], the impact of ship emissions on both gaseous and particulate pollutants has been investigated through an integrated methodology which includes atmospheric flow and numerical dispersion modelling as well as chemical composition and statistical analyses. BOLCHEM results showed that the impact of ship emissions covered an area of a few dozen kilometers and was 37.6% for NOx, −11.7% for O3, 4.3% for PM10, and 6.1% for PM2.5.…”
mentioning
confidence: 99%